Minimization of household hazardous solid waste (HHSW) with 4R concepts (reduce, reuse, recycle and recovery) in Padang City, Indonesia. (August 2019) - Ruslinda, Y; Raharjo, S; Dewilda, Y; Hidayatullah,; Aziz, R
Abstract: Improper management of hazardous waste originating from household activities will potentially pose a threat to health and the environment. Management of hazardous waste includes minimization activities and hazardous waste treatment. This study aims to analyze the existing conditions and potential minimization of Household Hazardous Solid Waste (HHSW) with the 4R concept, namely Reduce, Reuse, Recycle and Recovery in Padang City. HHSW minimization data was obtained through the analysis of questionnaire data distributed to several HHSW generation sources in Padang City, while the minimization potential was obtained from the existing literature review. The minimization of the existing HHSW was 17.4% (2, 067 kg/day) from the total HHSW generation in Padang City. This minimization activity consisted of 11.6% reduce activities, 2.2% reuse activities and 3.6% recycle activities. From the calculation and literature study, the potential of minimizing HHSW was 51.2% (6, 081 kg/day) which consists of 11.6% reduce potential in the form of large volumes of HHSW packaging purchases, 18.7% reuse potential through the return of product packaging to producers in the Environmental Producer Responsibility (EPR) program, 13.2% recycle potential in the form of oil can recycling, bulbs and cartridges, and 7.7% recovery potential by recovering metal content in batteries and car battery.